STUDY ON THE ACOUSTO-STRUCTURAL COUPLING OF THIN CYLINDRICAL HYDRAULIC PIPE - XIE MiaoXia; GUO Ruifeng; LI LiXia; ZHANG LinJie (Jixie qiangdu)
In thin hydraulic pipes,the interaction between acoustic field in the fluid and structural wave field may results in more energy loss.In order to make clear the energy loss mechanism of this kind of cylindrical pipe,an analytic study on the acousto-structural coupling of a thin cylindrical pipe is carried out using the impedance-mobility approach（ IMA） in this work.Coupled equations for describing such acousto-structural coupling are derived from the wave equation and the dynamic equation of a cylindrical shell.In deriving the dynamic equation of a cylindrical shell,wave propagation involving distortion of the cross section is considered,which is very different from general researches about hydraulic vibration.In order to validate the IMA model developed,the acousto-structural response of a cylindrical pipe filled with air is calculated using IMA and FEA,respectively,which reveals the good agreement between IMA and FEA results.